Dexamethasone is cost-effective alternative to ondansetron in preventing Post-Operative Nausea and Vomiting (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Postoperative nausea and vomiting (PONV) is a common complication of anesthesia and surgery. Numerous anti-emetics have been studied to prevent and treat PONV.Methods: This study evaluated the antiemetic efficacy, cost-effectiveness and clinical utility of prophylactic dexamethasone and ondansetron compared with placebo in prevention of postoperative nausea and vomiting after ENT surgery in 90 patients.Results: The incidence of PONV was significantly greater in placebo group than dexamethasone group and ondansetron group (p0.05. The incidence of early (0-6 h) PONV was significantly lower in dexamethasone group and ondansetron group than the placebo group (p 0.05). The incidence of PONV in the late postoperative period (6-24 h) was significantly lower in the dexamethasone group (3.33%) than the ondansetron group (23.33%) P